Media Appropriation by Local Communities and Popular Groups: Content Analysis of the Practical Media Activism Course Handbook Promoted by CONTAG - Andrade, Jhone Ricardo (2024)
This article aims to discuss the appropriation of media by popular communities based on the handbook of the media activism course offered by CONTAG. Content analysis was employed (Franco, 2012), drawing on concepts of media reframing, globalization, and the formation of the contemporary subject (Thompson, 2008; Silverstone, 2005; Santos, 1997; Giddens, 2002). In conclusion, it was observed that through media activism, communities in vulnerable conditions can harness new technologies, exploring their potentialities according to their needs in confronting the oppression of globalized capital.